Analysis of Supporting Factors in Performance Quality of Medan City Tourism Services for Free Daily Employees - Aisyah, Siti; Natasha, Syarifah Fadillah; Nazli, Putri; Anindya, Desy Astrid; Anggraini, Dwi Pertiwi; Habibie, Muhammad (Economic and Business Horizon, 2024)
The aim of this research is to see what factors determine the quality of performance of casual daily employees at the Medan City Tourism Office. The research method used is descriptive qualitative. By conducting observations and in-depth interviews, then compiling the data obtained to then use it as relevant information to support the research results. Based on the survey results and initial observations, researchers found several problems with the quality of performance of freelance daily employees of the Medan City Tourism Office. And this performance quality problem is caused by several factors, namely leadership style, education level, and employee discipline. Leadership in the form of leaders tends to make decisions themselves without involving team members, reducing opportunities for employees to participate and express their ideas. Casual Daily Employees (Pegawai Harian Lepas/PHL) in the Medan City Tourism Office are also required to be able to work outside working hours, while many employees are unable to work outside working hours. Education level is very important for job placement purposes, because without educational provision, people cannot easily learn something new. The level of education has a big impact on job placement, because each employee who has a higher level of education will have better intellectual skills and understand more easily when faced with new things compared to employees who only have a low level of education.